Pengembangan Media Digital Menulis Cerita Pendek Berbasis Kearifan Lokal Bugis di SMP Negeri 4 Tellu Siattinge - Syariani, Syariani; Sakaria, Sakaria; Hasriani, Hasriani (Fakultas Teknik Universitas Negeri Makassar, 2024)
This study aims to describe the feasibility of digital media for writing short stories based on Bugis local wisdom. The method used in this research is the research and development (R&D) method, with the development design of the 4D model (Define, Design, Development, and Dessimination). The data from this study are qualitative and quantitative data from expert and practitioner tests. The data analysis technique in this research is qualitative and quantitative data analysis. Qualitative data analysis is grouping data and concluding data in the form of comments, criticisms, suggestions from experts and practitioners of media improvement then, quantitative data analysis is finding the average of each indicator of expert and practitioner assessment for media feasibility. The results of this study showed the feasibility of media display obtained an average of 0.91 with a very feasible category, the feasibility of digital media programming writing short stories based on bugis local wisdom obtained 0.88 with a very feasible category, and the average of both expert and practitioner assessments obtained an average of 0.91 with a very feasible category.